The Irrigation sector - World Bank. South Asia Region Rural Development Sector Unit (Washington) (Washington World Bank, 1999)
The analysis of this report has found there US need for a major shift in India's irrigation strategy.This report prepared as part of the "India: Water Resources Management" sector work program jointly between the World Bank and Government of India
World Bank, South Asia Region Rural development Sector Unit in collaboration with the Government of India, Ministry of Water Resources
Keywords: Irrigation-India-Management; Water resources development-India; Agricultural productivity-India; Irrigation efficiency-India-Evaluation; Agriculture-Economic aspects-India